INFLUENCE OF THE PERSONAL POTENTIAL ON ADAPTATION OF YOUNG ENGINEERS IN THE SPHERE OF THE INDUSTRIAL PRODUCTION - Kotlyarova, Liubov; Sysoeva, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article analyzes the results of the experimental research of the young engineers’ peculiarities at the first job placement at the industrial plants. The participants of the research were tested while being graduates and then again as young specialists. In the researched sampling we have pointed out the groups with different degree of “adaptation” to the working activities factor: 36% with high level of adaptation, 31% with medium, and 33% with low adaptation. It is proved that 13% of the young specialists resign within the first months after the job placement in spite of the favourable conditions for the working activities. We have found out the reasons for resignation while interviewing the respondents. The survey of the successfully adapted young specialists has allowed to point out the factors that favourably influence the completion of the adaptation processes.Basing on the results of the tests aimed at the definition of the personal potential peculiarities, we have compiled characteristics for each group. We have demonstrated the influence of the students’ adaptation potential formed by the graduation on the effectiveness of the professional adaptation.